A Review of Rainfall Modelling for Rainfall Occurrence and Amount - Roslinazairimah, Zakaria; Muhammad Az-Zuhri, Azman; Noor Fadhilah, Ahmad Radi (2014)
Rainfall modelling is very important in water management and is frequently used especially in the field of algriculture, hydrology, climatology and industries. The lack of proper water management will results in negative consequences. There are two different types of rainfall modelling on any given time scales in which are based on the rainfall occurrence and rainfall amount will results in losing certain information of the rainfall features. Therefore, many researcher have tried to solve these weakness by consolidating the models of rainfall occurrence and rainfall amount simultaneously. Thus, this paper will review various types of rainfall models which have been used in modelling rainfall occurrence, rainfall amount or combination of both rainfall occurrence and rainfall amount.